Persistence and Protective Efficacy of a Mycobacterium tuberculosis Auxotroph Vaccine - Jackson, Mary (American Society for Microbiology, 1999)
New vaccines against tuberculosis are urgently required because of the impressive incidence of this disease worldwide and the highly variable protective efficacy of the current vaccine. The possibility of creating new live vaccines by the rational attenuation of strains from the Mycobacterium tuberculosis complex was investigated. Two auxotrophic mutants of M. tuberculosis and M. bovis BCG were constructed by disruption of one of their purine biosynthetic genes. These mutants appeared unable to multiply in vitro within mouse bone-marrow derived macrophages. They were also attenuated in vivo in the mouse and guinea pig animal models. In guinea pigs, the two mutants induced strong delayed-type hypersensitivity response to purified protein derivative. In a preliminary experiment, the two mutants were compared to the BCG vaccine for their protective efficacy in a challenge against aerosolized virulent M. tuberculosis in the guinea pig model. Both mutants conferred some level of protection. These experiments demonstrate that the rational attenuation of M. tuberculosis could lead to the design of new candidate live vaccines against tuberculosis.